Challenges for the development of an integrated agro-food-energy-biochemical nexus in Thailand. Issue 2 (3rd July 2017) - Sukphisal, Burin; Wongsurawat, Winai
Abstract : Purpose: This paper aims to synthesize the history of bio-refinery in Thailand and analyze the public policy challenges hindering the industry's growth and development since year 2000. Design/methodology/approach: The authors assembled dispersed data on the industry structure, history of investment and the current state of bio-refinery in Thailand from numerous public organizations and media outlets. The chronicle covers the initial launching and subsequent market growth of ethanol, biodiesel and bio-chemicals. The most innovative analysis in this study is the identification of the key players in the bio-refinery value chain. The authors supply insights about each player's stake, bargaining power, strategies and relative success/failure during the past few decades. Findings: Instead of working together to develop bio-refinery, it appears the Thai petroleum companies, policymakers and automotive companies often delay or block developments that would benefit bio-fuel and bio-chemical producers and crop growers. Conflicts of interests have caused policymakers and regulators to favor already overly protected industries. Seventeen years of bio-fuel policy from 2000 to 2016 has shown that the major objectives of the government's bio-fuel/bio-refinery policies have failed. Originality/value: Using Thailand as a case study, this paper illustrates the critical role of politics, special interest groups and lobbying in determining the viability of bio-fuel/bio-refinery industries in developing countries.